Development Of Stunted Toddlers Aged 24-59 Months Using Prescreening Developmental Questionnaire (Pdq) In Air Dingin Public Health Center, Padang 2019: An Overview - Dita Hasni; Febianne Eldrian; Anjas Adisena (Jurnal Ilmiah Kesehatan, 2021)
Background: Stunting is a chronic malnutrition problem that resulted from an insufficient nutritional intake for a long time. This problem can develop during pregnancy, infancy, childhood, and throughout the life cycle due to feeding that does not accommodate the nutritional needs. Stunting correlates with disorders of fine motor, gross motor, language, and personal social skills. Objective: This study aims to perceive an overview of stunted toddlers aged 24-59 months using the Prescreening Developmental Questionnaire (PDQ). Method: The authors carried out this research in Air Dingin public health center, Padang, from April to September 2019. This research was descriptive that included 40 toddlers aged 24-59 months diagnosed with stunting. The data presentation was a frequency distribution table and percentage. Results: This study obtained that 22 toddlers (55.0%) were girls, seven toddlers (17.5%) experienced a developmental deviation, and 26 toddlers (65%) had suspected developmental deviation. In short, there were several cases of stunted toddlers who underwent a developmental deviation